Pengaruh Transparasi dan Akuntabilitas Terhadap Pengelolaan Dana Desa di Kecamatan Sembawa Kabupaten Banyuasin - Dita Fetrisia Sonda; Maria; Yuli Antina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to find out how transparent and accountable the management of village funds is in Sembawa District, Banyuasin Regency. The population in the study were village officials in 11 villages in Sembawa District, Banyuasin Regency. Respondents in this research were 55 people using a saturated sampling technique. This type of research is quantitative research with primary data, namely distributing questionnaires to 11 villages in Sembawa District. The analytical method used is the multiple regression analysis method with SPSS 26 software. The results of the research show that transparency and accountability have an influence on village fund management in Sembawa District, Banyuasin Regency.